Pertanggungjawaban Buzzer Terkait Penggiringan Opini Publik Berdasarkan Hukum Positif Indonesia - Pranaja, Divellio; Narwastuty, Dian (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The activities of political buzzers in the digital space play a role in shaping and influencing public opinion through the dissemination of manipulative and organized information. This phenomenon raises legal issues because Indonesian positive law does not explicitly regulate the status and qualifications of political buzzer offenses. This study aims to analyze the criminal liability for political buzzer activities from the perspective of the New Criminal Code, the Electronic Information and Transactions Law, and the Broadcasting Law. The method used is normative juridical with a statutory and conceptual approach. The results show that although political buzzers have not been classified as a separate offense, their actions can still be held criminally liable as long as they meet the elements of an act, fault, unlawful nature, and cause harm to the public interest. The difficulty of proving and the anonymity of the perpetrators do not negate the criminal nature of these acts, but rather demonstrate the need for strengthened regulations and adaptive legal interpretation.